Funeral of the Constitution. - (:unkn) unknown (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
Hamlet. Act V. Scene a Church-yard. Enter two Clowns with spades.
1 print : col.
Keywords: Caricatures; Cartoons; York Minster Cathedral; Great Britain -- Relations -- Ireland; Catholic emancipation; St. Paul?s Cathedral (London, England); Constitutional history -- Great Britain; Shakespeare, William, 1564-1616 ? Hamlet.